The American Board of Sport Psychology
The American Board of Sport Psychology was established to evaluate and offer credentials in SPORT PSYCHOLOGY to qualified persons holding a regionally accredited Doctorate in PSYCHOLOGY (Ph.D., PsyD, Ed.D.)or who are licensed/certified as clinical and/or applied psychologists. Since the use of the occupational designation Psychologist is restricted by law, preventing practitioners without a doctorate in psychology from calling themselves Sport Psychologists, other certification bodies have created generic terms such as Sport Psychology Consultant, Sport Psychology Practitioner, Performance Enhancement Specialist, and Performance/Mental Coach to accommodate and entitle members with both psychology and non-psychology backgrounds under a common non-distinguishing title. Such designations often do not adequately reflect or convey the background and qualifications many doctorate holders in psychology and sport psychology have. Essentially, doctorate level psychologists have no official occupational or consultant's designation reflecting their unique training in psychology. Moreover there is no representative and training body or organization that is exclusively devoted to and concerned with psychologists and their presence in and practice of Sport Psychology. Fortunately, the specific credential Board Certified Sport Psychologist and advanced credential Board Certified Sport Psychologist-Diplomate, recognizing unique training and practice in psychology and contributions to sport psychology, along with continuing education is now available to qualified psychologists. The American Board of Sport Psychology also offers TRAINING, CERTIFICATION and RECOGNITION for MASTERS level PRACTITIONERS.